Analysis Of The Fraud Triangle Elements As Determinants Of Financial Shenanigans Risk Potential In Companies Listed In The Non-Banking Lq45 Index For The 2019-2021 Period - Wulandari, Sarah Ayu; Irianto, Gugus (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Financial shenanigans refer to deceptive acts by a company to make the company’s financial condition and performance appear good, stable, and interesting to users. As such, this research aims to quantitatively determine the empirical evidence of the effect of the fraud triangle elements on the financial shenanigans' risk. The population includes non-banking companies listed on the stock index of LQ45, from which 75 samples are selected through purposive sampling and analyzed by multiple linear regression utilizing SPSS ver.26. The results of the research exhibit that the financial need has a positive effect on financial shenanigans risk potential. In contrast, the effective monitoring and the change of external auditor do not affect financial shenanigans risk potential.